Glutamatergic and Resting-State Functional Connectivity Correlates of Severity in Major Depression – The Role of Pregenual Anterior Cingulate Cortex and Anterior Insula - Horn, Dorothea I.; Yu, Chunshui; Steiner, Johann; Buchmann, Julia; Kaufmann, Joern; Osoba, Annemarie; Eckert, Ulf; Zierhut, Kathrin; Schiltz, Kolja; He, Huiguang; Biswal, Bharat; Bogerts, Bernhard; et al. (Frontiers in Systems Neuroscience, 2010)
Glutamatergic mechanisms and resting state functional connectivity alterations have been recently described as factors contributing to Major Depressive Disorder (MDD). Furthermore, the pregenual anterior cingulate cortex (pgACC) seems to play an important role for major depressive symptoms such as anhedonia and impaired emotion processing. We investigated 22 MDD patients and 22 healthy subjects using a combined Magnetic Resonance Spectroscopy (MRS) and Resting State functional Magnetic Resonance Imaging (fMRI) approach. Severity of depression was rated using the 21-item Hamilton Depression Scale (HAMD) and patients were divided into severely and mildly depressed subgroups according to HAMD scores. Because of their hypothesized role in depression we investigated the functional connectivity between pgACC and left anterior insular cortex (AI). The sum of Glutamate and Glutamine (Glx) in the pgACC, but not in left AI, predicted the resting state functional connectivity between the two regions exclusively in depressed patients. Furthermore, functional connectivity between these regions was significantly altered in the subgroup of severely depressed patients (HAMD>15) compared to healthy subjects and mildly depressed patients. Similarly the Glx ratios, relative to Creatine, in the pgACC were lowest in severely depressed patients. These findings support the involvement of glutamatergic mechanisms in severe MDD which are related to the functional connectivity between pgACC and AI and depression severity.